TOWARD A PRACTICE OF CHRISTIAN ANTIHISTORY: WRITING THE ANTIHISTORY OF SOVIET COMMUNISM. - Sandle, Mark (Fides et historia, 2014)
The authors offer their perspective on Christian historians' writing of the history of communism in the Soviet Union, often referencing what is referred to the antihistory method of writing history of the Christian historian Johann Baptist Metz. An overview of the Metz's perspective on collective memory is provided.